Peran Kepemimpinan dan Budaya Organisasi dalam Meningkatkan Disiplin Kerja Pegawai pada SMAN 2 Praya - Fikri, Muhammad Khaerul; Cahyadi, Irwan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Work discipline is one of the key elements in supporting the success of an organization, as discipline reflects employees' compliance with established rules, regulations, and work responsibilities. The phenomenon of employee discipline at SMAN 2 Praya is still not optimal, as there are still delays every month. This study aims to analyze the Role of Leadership and Organizational Culture in improving employee Work Discipline at SMAN 2 Praya, as well as to determine which variable is more dominant. This research uses a quantitative type with a causal descriptive approach, with a questionnaire as an instrument that has been tested for validity and reliability. Data analysis was conducted using multiple linear regression, t-test, Dominance test, and coefficient of determination. The results of this study indicate that leadership and organizational culture have a positive and significant effect on employee work discipline at SMAN 2 Praya. The dominant test results show that organizational culture is the most dominant variable in influencing employee work discipline at SMAN 2 Praya, as it has the highest standard beta coefficient value compared to other variables.